2021
DOI: 10.3390/polym13132187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Femtosecond-Laser-Structured Injection Molding Tool on Mechanical Properties of the Manufactured Product

Abstract: During the injection molding process, the melt travels with a flow due to friction. As the velocity of the layers next to the wall is less than that of those flowing in the middle of the channel, a fountain flow is formed at the melt front. The temperature of the polymer surface decreases from the melt temperature to the contact temperature after contacting the mold surface. Based on all this, a complex shell–core structure is formed in injection-molded products, which can be influenced by the processing param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Another theory is the mechanical theory [16], according to which the surface to be bonded is never completely flat, so there are many peaks and valleys on the surface [17]. At one time, it was pseudo-suggested that adhesion was only created by the adhesive flowing into these voids, filling the microcavities, and when it made contact, the adhesive mechanically held the two bonded surfaces together.…”
Section: Introductionmentioning
confidence: 99%
“…Another theory is the mechanical theory [16], according to which the surface to be bonded is never completely flat, so there are many peaks and valleys on the surface [17]. At one time, it was pseudo-suggested that adhesion was only created by the adhesive flowing into these voids, filling the microcavities, and when it made contact, the adhesive mechanically held the two bonded surfaces together.…”
Section: Introductionmentioning
confidence: 99%